ปัจจัยที่มีความสัมพันธ์กับการตัดสินใจลงทุนคอนโดมิเนียม ของนักลงทุน ในเขตกรุงเทพมหานคร - นารีวงษ์ ศิริพงษ์; กุลิสร์ ณักษ์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
การวิจัยนี้มีความมุ่งหมาย เพื่อศึกษาปัจจัยที่มีความสัมพันธ์กับการตัดสินใจลงทุนคอนโดมิเนียม ของนักลงทุนในเขตกรุงเทพมหานคร กลุ่มตัวอย่างที่ใช้ในงานวิจัยครั้งนี้ คือนักลงทุนที่ลงทุนเพื่อขาย-ปล่อยเช่า รวมถึงลงทุนเพื่ออยู่อาศัยในระยะแรก หรือผู้ที่เคยลงทุนในคอนโดมิเนียมในรูปแบบต่างๆ ในเขตกรุงเทพมหานคร ที่มีอายุ 20 ปีขึ้นไป รวมขนาดกลุ่มตัวอย่างทั้งหมดคือ 400 คน ใช้แบบสอบถามในการเก็บรวบรวมข้อมูล สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน สถิติที่ใช้ทดสอบสมมติฐาน คือ การทดสอบค่าที การวิเคราะห์ความแปรปรวนทางเดียว การคำนวณค่าสถิติสหสัมพันธ์อย่างง่ายของเพียร์สัน และ สถิติการการวิเคราะห์เชิงถดถอยแบบพหุคูณ ผลการศึกษาพบว่า นักลงทุนส่วนใหญ่เป็นเพศหญิง อายุระหว่าง 20-29 ปี สถานภาพโสด การศึกษาระดับปริญญาตรี อาชีพพนักงานรัฐวิสาหกิจ รายได้ ต่ำกว่าหรือเท่ากับ 15,000 บาท มีประสบการณ์ลงทุนน้อยกว่า 1 ปี ระยะเวลาถือครองหลักทรัพย์น้อยกว่า 1 ปี มีแหล่งข้อมูลในการตัดสินใจลงทุน คือ แหล่งบุคคล มีระดับความรู้ความเข้าใจเกี่ยวกับการลงทุนระดับมาก และนักลงทุนส่วนใหญ่ให้ความสำคัญกับสภาพแวดล้อมทางธุรกิจโดยรวมอยู่ในระดับมาก และให้ความสำคัญกับปัจจัยความสำเร็จ 10 ประการโดยรวมอยู่ในระดับมากที่สุด This research aimed to study factors relating to investors’ investment decision on condominiums in the Bangkok metropolitan area. The respondents in this research are investors who invest in selling-renting, including investors who invested to live during first period and people who had invested in a condominium in various forms in Bangkok, and the respondents were age twenty and above. The samples used in this study consisted of four hundred respondents. The questionnaire was constructed and used as a tool for collecting data. The statistics used to analyze the data were percentage, mean, standard deviation, t-test and one-way analysis of variance, Pearson product moment correlation coefficient analysis, and multiple regression statistical analysis. The results of this research were as follows: The most investors were female that had age between 20-29 years old with single status. Their education levels were Bachelor Degree. Their career were state enterprise officers. Their revenue per month were below or equal to THB 15,000. They had investment experiences less than 1 year. The time period holding properties less than 1 year. There were sources of information for investment decision such as Personnel sources and there was the cognitive level related to the investment in the highest level. The most investors placed importance of overall business environment in high level. And, the most investors placed importance of overall the 10 factors of Rubik Model in highest level.